Mini Review: linkages between essential tremor and Parkinson’s disease? - Wu, Yiwen; Ding, Jianqing; Gao, Yuan; Chen, Shangdi; Li, Li; Li, Rena (Frontiers in Cellular Neuroscience, 2013)
Essential tremor (ET) and Parkinson’s disease (PD) are two of the most common movement disorders. Tremors are the primary symptoms of ET and of some PD patients, the two are often mistaken for each other. Especially since there are no available differentiate tests for the tremor of ET or PD, the early diagnoses mainly based on clinical assessments of medical symptoms, family and medication history, and examination by physicians. There is increasing evidence suggesting an association between ET and PD, such as a similar tremor frequency, overlapping resting tremors (a typical PD tremor), postural tremors (mainly in ET patients) in both ET and PD patients, and many ET patients develop PD later in life. Although it is difficult to make a differential diagnosis of ET and tremor-dominant PD based on clinical assessment, recent developments of objective measurements, such as brain imaging, neuropathology, and genetic analysis, has opened a helpful window for distinguishing ET from PD. In this mini review, we included literatures of ET and PD studies and discussed various advanced methods for differential diagnosis between ET and PD such as neuroimaging, genetic markers, tremor intensity and frequency, and drug-responses.